The Effect of Handedness and Task Difficulty on Effective Target Width and Temporal Accuracy in Fitts' Speed-Accuracy Tradeoff Task - Mohammadreza Doustan; Leila Farzad; Esmaeel Saemi; Maliheh Niknam (University of Tehran, 2019)
The aim of this study was to investigate the effect of handedness and task difficulty on effective target width and temporal accuracy of the Fitts' speed-accuracy tradeoff task. The present study was semi-experimental and the tools used included Edinburgh handedness questionnaire, light pen, speed-accuracy measurement device, laptop, chronometer, and metronome. The statistical population consisted of students aged between 14 and 15. The sample included 20 students who participated in this study by convenience sampling method. They were divided into two groups: left-hand and right-hand (each group 10 subjects). Each participant performed 4 trials (each trial 30 seconds) of dual target tapping task in rhythm with the metronome sound. The trials consisted of two easy and difficult tasks and each subject performed each task with dominant and not-dominant hands in rhythm with the metronome sound set up at 300 milliseconds. For statistical analysis of data, variance analysis with repeated measures was used at the significance level of 0.05. The results showed that in dominant hand, the handedness and difficulty of the task had no significant effect on the effective width of the target (P=0.973, P=0.611). Also, the handedness did not affect the average time lag (P=0.135, P=0.785), but in non-dominant hand, the average time lag was more for the difficult task than the simple task (P=0.001). In difficult tasks, participants seem to be trying to keep the spatial error rate constant by reducing the speed of the movement and to sacrifice speed for the spatial accuracy. Also, the time error (mean lag) is more influenced by the difficulty of the task than the handedness.